Incidence of symptomatic Lyme borreliosis in nine European countries - Frederick J. Angulo; Emily Colby; Anne-Mette Lebech; Per-Eric Lindgren; Anna Moniuszko-Malinowska; Franc Strle; Julia Olsen; Gordon Brestrich; Andrew Vyse; Madiha Shafquat; L. Hannah Gould; Patrick H. Kelly; et al. (International Journal of Infectious Diseases)
Objectives: To better understand the Lyme borreliosis (LB) burden in Europe, we aimed to estimate the incidence of symptomatic Borrelia burgdorferi sensu lato (Bbsl) infections after adjusting public health LB surveillance data for under-detection of symptomatic Bbsl infections. Methods: Data from seroprevalence studies and estimates of the symptomatic proportion and duration of antibody detection in Bbsl-infected individuals, derived from reviews of the published literature, were used to adjust public health LB surveillance data to estimate the incidence of symptomatic Bbsl infection in nine European countries from 2018 to 2022. Results: The prevalence of anti-Bbsl antibodies ranged from 2.3% in Romania to 9.4% in Germany. Under-detection multipliers varied across surveillance systems; using 10-year duration of antibody detection, multipliers were 2.4-10.5 in countries reporting all LB cases and 54.6-722.2 in countries reporting only Lyme neuroborreliosis cases. The incidence of symptomatic Bbsl infection adjusted for under-detection was highest in Finland, Germany, Norway, Poland, and Switzerland, intermediate in the Czech Republic and Denmark, and lowest in Ireland and Romania. Conclusion: Adjustment of LB surveillance for under-detection found a high incidence of symptomatic Bbsl infection in several European countries. Differences in LB surveillance systems should be considered when comparing surveillance data between countries and when estimating LB disease burden.